The Mental Health Effects of Assisted Reproductive Technology - Malham, Shae (East Carolina University, 2022)
In this research project, I explored how mental health and undergoing ART are intertwined. Through a literature review, published researched about mental health and its relation to ART was reviewed to find key information regarding the mental health effects of ART. Following the literature review, interviews were conducted with seven women to gain a better understanding of their lived experiences undergoing ART treatments. The purpose of this study was to learn more about the lived experiences of women who go through fertility treatments and how the journey through infertility and trying to conceive a child influences their mental health.
Keywords: Mental Health, ART treatment, and Women's Health